Condições sanguíneas e gengivais em pacientes alérgicos ao níquel submetidos a tratamento ortodôntico com braquetes convencionais e níquel free - Camila Alessandra Pazzini (2012)
The aim of the present study was to assess gingival status and blood parameters one month after the removal of braces in patients with nickel allergy. Ninety-six patients were initially evaluated. Allergy to nickel was diagnosed using a patch test. After the determination of the prevalence of those allergic to nickel, two groups were formed: 16 allergic and 16 non-allergic patients. Gingival status was determined using the gingivalindex. Humoral characteristics were determined through a complete blood test, including the quantification of nickel in the blood and IgE levels. Assessments of periodontal status were determined by a single, blinded, duly calibrated examiner and blood samples were taken after nine months of treatment and one month after removing the orthodontic appliances. Statistical analysis involved paired and non-paired t-tests,the Mann-Whitney, Wilcoxon, McNemar and linear trend chi-square tests (p.0.05). The number of eosinophils, basophils and monocytes increased, whereas the number of bands decreased between periods in the allergic group compared with controls (p<0.05). The number of lymphocytes increased significantly in the control group (p<0.05).Gingival index scores decreased significantly in both groups during and after treatment. The results of the present study analyzing the period of direct contact with the allergenic agent and after its removal indicate that orthodontic treatment with conventional stainless steel appliances does not initiate or aggravate a hypersensitive reaction to nickel.